Prevalencia del sobrepeso y obesidad como indicador de riesgo en las enfermeras y enfermeros de quirófano y recuperación en el Hospital San Francisco de Quito durante el primer semestre 2017 - Bastidas Robalino, Andrea Carolina (2017)
Overweight and obesity are chronic diseases that comprise 62.8 percent of the Ecuadorian population. Excess weight and the distribution of body fat is determined with a BMI greater than 25 kg / m2 and with abdominal circumference greater than 80 cm in women and greater than 94 in men, measures equivalent to an increased risk of cardiovascular diseases, diabetes mellitus, hypertension, dyslipidemias, colon cancer, stomach, among others. The treatment is based on eradicating the causal factors with physical activity and a healthy and balanced diet. The objective of this research is to determine the prevalence of overweight and obesity as an indicator of risk of morbidity and mortality in nurses and nurses. A quantitative descriptive cross-sectional study was carried out on 25 nursing graduates (22 women and 3 men) between 22 and 59 years old, who were taken anthropometric measures to calculate the body mass index and waist / hip index, the blood pressure and capillary glycemia and evaluated the predisposing factors. The results showed that the prevalence of overweight in women is 41 percent and 33 percent in men and 18 percent of nurses and 33 percent of nurses suffer from obesity. Abdominal obesity was found in 86 percent of women and 33 percent of men, due to this, nurses and fueros make up a group with a high risk of suffering concomitants associated with obesity that is mainly attributed to sedentary lifestyle and consumption. foods with a high intake of fat and carbohydrates.